PENGARUH DIMENSI INKLUSI KEUANGAN DAN FINTECH TERHADAP PERTUMBUHAN EKONOMI NEGARA BERKEMBANG DI ASIA DENGAN INDEKS INKLUSI KEUANGAN TINGGI - Saraswati, Birgitta Dian (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
This study aims to determine the effect of access dimensions, availability dimensions, usage dimensions as indicators of financial inclusion and fintech on economic growth in Indonesia, India, Thailand, the Philippines and Cambodia which are developing countries in Asia with a high level of financial inclusion. The data used is a combined panel data between the crosssection data of the five countries and the time series in the 2015-2019 time period. By using the Fixed Effect Model (FEM) method, this study shows that the availability dimension with the number of commercial bank branch offices has a significant effect in a negative direction and the usage dimension with loans disbursed by commercial banks has a significant positive effect on economic growth. While the access dimension with indicators of ownership of commercial bank savings accounts and payment fintech has no significant effect on economic growth.